A method for personalising the blade size for competitors in flatwater kayaking - Sprigings, E.; McNair, P.; Mawston, G.; Sumner, D.; Boocock, M. (Sports Engineering, 2006)
The intent of this project was to explore the feasibility of personalising the paddle blade size for individual flatwater kayakers based on their power output profiles. Twelve elite male kayakers performed on a kayak ergometer at the same intensity and resistance that they would normally experience while paddling at race pace for 500 m on the water. The kayak ergometer was instrumented so that power profiles could be determined from the instantaneous force and velocity of the representative centre point of the paddle blade. From the power profile information, the researchers calculated a personalised blade size that was expected to improve performance for those kayakers differing more than 5% from the calculated `ideal` size. For the elite kayakers studied, it was recommended that seven of the paddlers should increase their blade size by approximately 5-10%. For the remaining five paddlers, the results indicated that their current blade sizes were within the expected measurement error of their predicted ideal value and should be retained. It is anticipated that this research will provide the theoretical rationale for elite kayakers to see the need to personalise their blade size based on their own muscle power profiles.